The recyclable waste recycling potential towards zero waste cities - A comparison of three cities in China. (1st May 2021) - Gu, Binxian; Tang, Xinyi; Liu, Lingxuan; Li, Yuanyuan; Fujiwara, Takeshi; Sun, Haohui; Gu, Aijun; Yao, Yanbing; Duan, Ruiyang; Song, Jie; Jia, Renfu
Abstract: Recycling is an essential practice for the successful operation of zero waste cities. It is essential to understand the recyclable waste recycling potential (RWRP). This study quantifies the RWRP of different cities in China. Suzhou, Yangzhou, and Suqian represent high-, middle- and low-income cities, respectively. The RWRP statistics are based on systematic multiple longitudinal tracking field surveys conducted between 2016 and 2019. Obvious RWRP spatio-temporal disparities were observed between inter-city and intra-city. For instance, Suzhou showed a slight increase in high resource value paper; Yangzhou had a slight increase in low resource value paper; and Suqian had a huge increase in no resource value paper and plastic. Additionally, more recyclable organics were generated in the old districts of Suzhou, and they were also predominant in the new districts of Yangzhou. No significant difference was observed in recyclable organics and recyclable material in Suqian. However, recyclable organics is a constant, while recyclable material fluctuates in the case cities. Household consumption structure has a major impact on RWRP. Other factors, such as economic development, urban resident population, consumption preferences, local customs and culture, as well as residential lifestyles also affect RWRP. This study proposes three policies: 1) to establish flexible and carefully planned recycling strategies, 2) to develop the distribution market of composting products, and 3) to incorporate economic and demographic initiatives to develop a workable recycling policy that can lead to zero waste implementation in the future. The zero waste concept was further assessed by the authors' review of 69 cities worldwide based on previous research. We compared past results with the three featured cities in this study and 35 other Chinese cities, thereby presenting a world view of zero waste potential. It is anticipated that representative cities' RWRP quantification and policy implementations can be a model for municipal solid waste management and recycling policies in other Chinese cities, which will help them transition to zero waste cities and probably provide a model for cities worldwide. Graphical abstract: Image 1 Highlights: A longitudinal survey was performed in 3 cities with different income levels. Recycling potential and recyclable waste stream generation were quantitated. Spatiotemporal disparity effects on recycling potential are discussed. Practical recycling policies are suggested with zero waste goals in the future.